Flexibility Work Arrangements and Employee Normative Commitment in Selected General Hospitals in Delta State, Nigeria - Ugo Chuks Okolie; Thomastina Nkechi Egbon (Universitas Kuningan, 2023)
This study examined flexible working arrangements and employee normative commitment in selected hospitals in Delta State. Specifically, to access the influence of flexi-time, job-sharing and telecommuting on employee normative commitment. A cross-sectional research design and simple random sampling technique was adopted. A questionnaire was employed as the research instrument for the study with 173 respondents deemed usable. The study was anchored on border theory and data collected were analysed using descriptive and inferential statistics. Correlation and multiple regression analysis were employed to analysed the study hypotheses. The results showed that flex-time and telecommuting significantly influence employee normative commitment while sharing did not significantly influence employee normative commitment. The study concludes that flexi-time, job-sharing and telecommuting jointly significantly influenced employee normative commitment. Therefore, the study recommends among others that there should be well detailed policies that will guide both the hospital management and their employees on flexible working arrangements.